Peran Fasilitator PUSPAGA dalam Manajemen Event Pelayanan Program Pusat Pembelajaran Keluarga Tingkat Balai RW X Ketabang Kota Surabaya. - Restiatin, Restiatin; Kusuma, Yanda Bara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The research aims to determine the role of puspaga facilitators in event management for family learning center program services at RW X Ketabang hall level, Surabaya City. Puspaga is a learning tool for families in the city of Surabaya to improve their ability to overcome problems related to violence, delinquency among women and children and other problems in the family environment. This research uses a qualitative approach with descriptive research methods. The research uses data collection techniques by means of observation and taking documentation. The results of the research that has been carried out show that the Puspaga Facilitator has been able to manage the event management of the Puspaga program services carried out at the RW.